1986
DOI: 10.1093/cvr/20.9.679
|View full text |Cite
|
Sign up to set email alerts
|

A geochemical basis for endomyocardial fibrosis

Abstract: In a search for geochemical factors that could play a role in the pathogenesis of tropical endomyocardial fibrosis, endomyocardial tissue samples obtained from patients at necropsy or operation were analysed for major elements present in laterite and monazite, which are important soil constituents of Kerala State of India. Atomic absorption spectrophotometry was used for detecting iron, silicon, aluminium, zinc, magnesium, calcium, sodium, potassium, and manganese and neutron activation analysis for thorium. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The etiology of the disease is unknown, however it has been associated with a number of factors including tropical climate, helminthic infections and eosinophilia, certain cardiotropic viruses, ingestion of certain foods like cassava, combination of magnesium deficiency and high levels of cerium in the body [8][9][10][11]. No such factors were found in our patient.…”
Section: Discussionmentioning
confidence: 63%
“…The etiology of the disease is unknown, however it has been associated with a number of factors including tropical climate, helminthic infections and eosinophilia, certain cardiotropic viruses, ingestion of certain foods like cassava, combination of magnesium deficiency and high levels of cerium in the body [8][9][10][11]. No such factors were found in our patient.…”
Section: Discussionmentioning
confidence: 63%
“…A clustering of EMF in the coastal region of Kerala led to an hypothesis that exposure to geochemical substances may affect EMF. In support of this, cerium, a rare earth element, was found in the hearts of EMF patients in greater abundance than controls (Valiathan et al 1986), a finding that requires confirmation.…”
Section: Discussionmentioning
confidence: 88%
“…Another peak appears around age 30, favouring women 2 : 1 over men (Connor et al 1967(Connor et al , 1968Sezi 1993). EMF is prevalent in Kerala State, India, and in Uganda, where more detailed studies have been done (Connor et al 1967(Connor et al , 1968Valiathan et al 1993). In Kerala, EMF clusters along the coastal area, and in Uganda the condition is most prevalent in the south central districts of Mukono and Luwero (formerly East Mengo).…”
Section: Introductionmentioning
confidence: 99%
“…As with industrial exposure, environmental contact with lanthanoid dusts is associated fibrotic tissue injury. Of interest, environmental exposure to cerium is linked to fibrotic cardiomyopathy rather than to lung fibrosis [4648]. The underlying mechanism of this is not known, but it has been demonstrated that cardiac fibroblasts respond to challenge with a greater proliferative response than do lung fibroblasts [49,50].…”
Section: Discussionmentioning
confidence: 99%